If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + 10x = 50 + 5x Solving 20 + 10x = 50 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 20 + 10x + -5x = 50 + 5x + -5x Combine like terms: 10x + -5x = 5x 20 + 5x = 50 + 5x + -5x Combine like terms: 5x + -5x = 0 20 + 5x = 50 + 0 20 + 5x = 50 Add '-20' to each side of the equation. 20 + -20 + 5x = 50 + -20 Combine like terms: 20 + -20 = 0 0 + 5x = 50 + -20 5x = 50 + -20 Combine like terms: 50 + -20 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 4t=2t-26 | | 7y=-21 | | 18x^2-98=0 | | x^4-12x^2-28=0 | | 2x-18=(15-11) | | 9h-3.2-10h=6 | | -4(-3x+2)=8(4x-6) | | 5x^5-x^4-25x^3-5x^2+2x=0 | | -9(t+4)=18 | | 6(9)-6= | | 5(2)+8= | | -3y+7c=a | | 7(8)+10= | | 6g+11-2g=31 | | 15=7(x-y)+3x | | 5a+6+2a=12 | | -4(1)-10= | | 7-6x=15+2x | | -4(6)-4= | | (x-1)(x-6)=0 | | -3y+7y=a | | 2.85y-7=12.85y-3 | | 8(4)+5= | | 50+30x=75+25x | | 5(9+6)=5(6)+5(9) | | 4(3)+7= | | 3x+12=5(x+y) | | -5(7)-10= | | -4(10)-3= | | y=-5x^2+40x-5 | | -9(7)-9= | | 4x-7=5x+4 |